Frugal Living as an Islamic Character Education Strategy: a Study of the Implementation of the Values of Zuhud and Qana'ah - Wardatul Hamro; Siti Halimah (JIE (Journal of Islamic Education), 2026)
The growing influence of consumer culture in the digital era has posed significant challenges to the development of Islamic character among adolescents, particularly in fostering simplicity, self-restraint, and responsible consumption. This study aims to examine the implementation of frugal living as an Islamic character education strategy grounded in the values of zuhud and qana’ah at MTs Wahid Hasyim Bangil, East Java, Indonesia. Employing a qualitative case study design, the research involved five participants, consisting of the principal, an Aqidah Akhlak teacher, a curriculum coordinator, and two students. Data were collected through participant observation, semi-structured interviews, and documentation and were analysed using the interactive model of data analysis developed by Miles, Huberman, and Saldaña. The trustworthiness of the findings was ensured through source triangulation, methodological triangulation, and member checking. The findings reveal that frugal living is implemented through three interrelated strategies: value-based learning, continuous habituation, and teacher role modeling. These strategies facilitate the internalisation of zuhud and qana’ah by encouraging students to differentiate between needs and desires, regulate consumptive tendencies, cultivate gratitude, and utilise resources responsibly. The study further identifies social media exposure, peer influence, and contemporary consumer culture as key challenges affecting the sustainability of these values among adolescents. The originality of this study lies in positioning frugal living not merely as a financial management practice but as an integrative Islamic character education model that combines spiritual values, behavioral habituation, and social learning processes. The findings suggest that frugal living represents a relevant and adaptive educational approach for strengthening Islamic character formation and promoting responsible lifestyles among students in the digital age.